1869 Neb. Laws 53 - (:unkn) unknown (My University, 1869)
An Act To Incorporate Cities Of The First Class In The State Of Nebraska, § 47: Allowed the city council to license vendors of gunpowder.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER